Endothelial Cell‐Specific Prolyl Hydroxylase‐2 Deficiency Augments Angiotensin II–Induced Arterial Stiffness and Cardiac Pericyte Recruitment in Mice - Bo Liu; Heng Zeng; Han Su; Quinesha A. Williams; Jessie Besanson; Yingjie Chen; Jian‐Xiong Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Endothelial prolyl hydroxylase‐2 (PHD2) is essential for pulmonary remodeling and hypertension. In the present study, we investigated the role of endothelial PHD2 in angiotensin II–mediated arterial stiffness, pericyte recruitment, and cardiac fibrosis. Methods and Results Chondroitin sulfate proteoglycan 4 tracing reporter chondroitin sulfate proteoglycan 4– red fluorescent protein (DsRed) transgenic mice were crossed with PHD2flox/flox (PHD2f/f) mice and endothelial‐specific knockout of PHD2 (PHD2ECKO) mice. Transgenic PHD2f/f (TgPHD2f/f) mice and TgPHD2ECKO mice were infused with angiotensin II for 4 weeks. Arterial thickness, stiffness, and histological and immunofluorescence of pericytes and fibrosis were measured. Infusion of TgPHD2f/f mice with angiotensin II resulted in a time‐dependent increase in pulse‐wave velocity. Angiotensin II–induced pulse‐wave velocity was further elevated in the TgPHD2ECKO mice. TgPHD2ECKO also reduced coronary flow reserve compared with TgPHD2f/f mice infused with angiotensin II. Mechanistically, knockout of endothelial PHD2 promoted aortic arginase activity and angiotensin II–induced aortic thickness together with increased transforming growth factor‐β1 and ICAM‐1/VCAM‐1 expression in coronary arteries. TgPHD2f/f mice infused with angiotensin II for 4 weeks exhibited a significant increase in cardiac fibrosis and hypertrophy, which was further developed in the TgPHD2ECKO mice. Chondroitin sulfate proteoglycan 4 pericyte was traced by DsRed+ staining and angiotensin II infusion displayed a significant increase of DsRed+ pericytes in the heart, as well as a deficiency of endothelial PHD2, which further promoted angiotensin II–induced pericyte increase. DsRed+ pericytes were costained with fibroblast‐specific protein 1 and α‐smooth muscle actin for measuring pericyte–myofibroblast cell transition. The knockout of endothelial PHD2 increased the amount of DsRed+/fibroblast‐specific protein 1+ and DsRed+/α‐smooth muscle actin+ cells induced by angiotensin II infusion. Conclusions Knockout of endothelial PHD2 enhanced angiotensin II–induced cardiac fibrosis by mechanisms involving increasing arterial stiffness and pericyte–myofibroblast cell transitions.